TAFSSA District Agrifood Systems Assessment in Bangladesh 2023: Retail Survey - International Rice Research Institute; International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at advancing equitable access to sustainable healthy diets, enhancing farmers' livelihoods and resilience, and conserving natural resources such as land, air, and water across South Asia. The TAFSSA district agrifood systems assessment seeks to establish a robust, accessible, and integrated evidence base that connects farm production, market access, dietary patterns, climate risk responses, and natural resource management, with gender considerations integrated throughout. The assessment focuses on rural areas in Bangladesh, India, and Nepal, utilizing a district-level, multi-year approach. Data collection took place between February and June 2023 in the Rangpur and Rajshahi districts of Bangladesh. The survey covered 50 villages in each district, focusing on formal and informal multi-vendor markets offering a variety of food products within a 10-kilometer radius of the village centroid. The types of multi-vendor markets included in the survey were village markets, weekly village markets, roadside/street markets, and wholesale markets (mandis). The survey employed pretested, structured questionnaires organized into four distinct modules: 1. Market Manager Module: Captures general information about the market as a whole. 2. Interview-Based Module: Gathers vendor-specific data, including details on the assortment of goods, availability, resilience, food sourcing, wastage, access, and protection dimensions. 3. Observation + Photo Module: Focuses on market infrastructure, food quality, safety, and hygiene, supplemented with photographic documentation. 4. Food List Module: Documents the availability and prices of an extensive range of food items at each location.